Antimicrobial Resistance in Streptococcus pneumoniae before and after the Introduction of Pneumococcal Conjugate Vaccines in Brazil: A Systematic Review - Patricia Alice Knupp-Pereira; Amanda Seabra Cabral; Ítalo Moraes Dolores; Amanda Beiral da Silva; Helvécio Cardoso Correa Póvoa; Felipe Piedade Gonçalves Neves (MDPI AG, 2024)
Streptococcus pneumoniae causes serious illnesses, such as pneumonia, bacteremia, and meningitis, mainly in immunocompromised individuals and those of extreme ages. Currently, pneumococcal conjugate vaccines (PCVs) are the best allies against pneumococcal diseases. In Brazil, the 10-valent and 13-valent PCVs have been available since 2010, but the threat of antimicrobial resistance persists and has been changing over time. We conducted a systematic review of the literature with works published since 2000, generating a parallel between susceptibility data on isolates recovered from colonization and invasive diseases before and after the implementation of PCVs for routine childhood use in Brazil. This systematic review was based on the Cochrane Handbook for Systematic Reviews of Interventions and Preferred Reporting Items for Systematic Literature Reviews and Meta-Analyses (PRISMA) guidelines. Despite the inclusion of PCVs at a large scale in the national territory, high frequencies of non-susceptibility to important drugs used in pneumococcal diseases are still observed, especially penicillin, as well as increasing resistance to macrolides. However, there are still drugs for which pneumococci have a comprehensive sensitivity profile.